Immuno-metabolic stress responses control longevity from mitochondrial translation inhibition in C. elegans - Iman Man Hu; Marte Molenaars; Yorrick R. J. Jaspers; Bauke V. Schomakers; Michel van Weeghel; Amber Bakker; Melanie Modder; Joseph P. Dewulf; Guido T. Bommer; Arwen W. Gao; Georges E. Janssens; Riekelt H. Houtkooper (Nature Communications)
Abstract Perturbing mitochondrial translation represents a conserved longevity intervention, with proteostasis processes proposed to mediate the resulting lifespan extension. Here, we explore whether other mechanisms may contribute to lifespan extension upon mitochondrial translation inhibition. Using multi-omics and functional in vivo screening, we identify the ethylmalonyl-CoA decarboxylase orthologue C32E8.9 in C. elegans as an essential factor for longevity induced by mitochondrial translation inhibition. Reducing C32E8.9 completely abolishes lifespan extension from mitochondrial translation inhibition, while mitochondrial unfolded protein response activation remains unaffected. We show that C32E8.9 mediates immune responses and lipid remodeling, which play crucial roles in the observed lifespan extension. Mechanistically, sma-4 (a TGF-β co-transcription factor) serves as an effector of C32E8.9, responsible for the immune response triggered by mitochondrial translation inhibition. Collectively, these findings underline the importance of the “immuno-metabolic stress responses” in longevity upon mitochondrial translation inhibition and identify C32E8.9 as a central factor orchestrating these responses.